2019
DOI: 10.1519/jsc.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological and Kinematic Demands of Wheelchair Basketball Games—A Review

Abstract: Seron, BB, Oliveira de Carvalho, EM, and Greguol, M. Analysis of physiological and kinematic demands of wheelchair basketball games—A review. J Strength Cond Res 33(5): 1453–1462, 2019—In wheelchair basketball (WB), knowledge of the specificities of the game is essential for efficient planning of training strategies for high performance. This study aimed to review the literature concerning studies that have investigated physiological and kinematic measures during WB games. The literature search took place in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…Several authors have related functional classification with different parameters, for instance, Vanlandewijck et al [ 28 ] observed that the upper classifications (category B, 3–4.5 classes) had better results in total amount of actions performed per time played, while Molik et al [ 29 ] showed that athletes with active pelvic control (category B) demonstrated greater peak power output and mean power output than the group without control (category A, 1.0–2.5 classes) in an anaerobic Wingate test. Our findings were in line with previous literature, in which upper WB classes (3 to 4.5) had better results, but no significant differences were found between the two groups for field tests sprint performance [ 9 , 13 , 14 ]. Even more, to our knowledge no studies have been performed to accurately describe the velocity curve of WB for the 5F, neither for the tests presented in this research.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several authors have related functional classification with different parameters, for instance, Vanlandewijck et al [ 28 ] observed that the upper classifications (category B, 3–4.5 classes) had better results in total amount of actions performed per time played, while Molik et al [ 29 ] showed that athletes with active pelvic control (category B) demonstrated greater peak power output and mean power output than the group without control (category A, 1.0–2.5 classes) in an anaerobic Wingate test. Our findings were in line with previous literature, in which upper WB classes (3 to 4.5) had better results, but no significant differences were found between the two groups for field tests sprint performance [ 9 , 13 , 14 ]. Even more, to our knowledge no studies have been performed to accurately describe the velocity curve of WB for the 5F, neither for the tests presented in this research.…”
Section: Discussionsupporting
confidence: 93%
“…Even more, the controversy between outcomes limits the future development, for instance, when dealing with the role of trunk stabilization in WB functional classification [ 7 , 8 ]. Also, most of the studies analyzing physiological and biomechanical features of this sport framed their results using the WB classification system [ 9 ], therefore it is accepted in the literature its use to provide practical application and guidance of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In basketball, a proper pitching arc can improve the hitting rate. erefore, many studies have been conducted to analyze the kinematic characteristics in basketball sports videos [2,3]. Good basketball players throw the ball with a nice arc, proper downward spin, and minimal lateral deviation from the optimal shooting plane.…”
Section: Introductionmentioning
confidence: 99%
“…Edwards) appears to be more suitable for quantifying the physiological stress of WB athletes. 13 For the training control context, the use of the HR-based and RPE-based methods is suggested, because although they provide different information, both methods may be complementary. 14…”
Section: Introductionmentioning
confidence: 99%